International Law and Ageism (Polish Yearbook of International Law, 2016)
In the 21st century ageism is becoming the most widely spread phenomenon. It has become so extensive that presently many more seniors in Europe are exposed to ageism than other people to sexism or racism. Contrary to other vulnerable groups, the elderly do not enjoy any binding instrument that could protect them and their dignity against ageism in the same way that women and racial groups are protected against sexism and racism. Unfortunately, the UN General Assembly resolution, supposed to be a first step to drawing up such a convention, was adopted with a significant number of abstentions, leaving the fate of a potential treaty on the rights of the elderly uncertain. On the other hand, in 2014 the Committee of Ministers of the Council of Europe adopted a new recommendation, and in June 2015 members of the Organisation of American States adopted a treaty protecting the elder’s rights. Taking into account these new circumstances, the idea underlying this article is to investigate the ability of international instruments to limit ageism and protect older persons’ dignity, as well as to indicate existing gaps.